Improving Medicare's Hospital Compare Mortality Model. (14th March 2016) - Silber, Jeffrey H.; Satopää, Ville A.; Mukherjee, Nabanita; Rockova, Veronika; Wang, Wei; Hill, Alexander S.; Even‐Shoshan, Orit; Rosenbaum, Paul R.; George, Edward I.
Abstract : Objective: To improve the predictions provided by Medicare's Hospital Compare (HC) to facilitate better informed decisions regarding hospital choice by the public. Data Sources/Setting: Medicare claims on all patients admitted for Acute Myocardial Infarction between 2009 through 2011. Study Design: Cohort analysis using a Bayesian approach, comparing the present assumptions of HC (using a constant mean and constant variance for all hospital random effects), versus an expanded model that allows for the inclusion of hospital characteristics to permit the data to determine whether they vary with attributes of hospitals, such as volume, capabilities, and staffing. Hospital predictions are then created using directly standardized estimates to facilitate comparisons between hospitals. Data Collection/Extraction Methods: Medicare fee‐for‐service claims. Principal Findings: Our model that included hospital characteristics produces very different predictions from the current HC model, with higher predicted mortality rates at hospitals with lower volume and worse characteristics. Using Chicago as an example, the expanded model would advise patients against seeking treatment at the smallest hospitals with worse technology and staffing. Conclusion: To aid patients when selecting between hospitals, the Centers for Medicare and Medicaid Services (CMS) should improve the HC model by permitting its predictions to vary systematically with hospital attributes such as volume, capabilities, and staffing.